Acaulosproa koreana, a New Species of Arbuscular Mycorrhizal Fungi (Glomeromycota) Associated with Roots of Woody Plants in Korea - Eun-Hwa Lee (Mycobiology, 2018)
A new species of arbuscular mycorrhizal fungi (Glomeromycota), Acaulospora koreana, was isolated from forest soils in South Korea. This novel fungus was collected from the rhizosphere of Lindera obtusiloba and Styrax obassia in forest and propagated with Sorghum bicolor in pot. Morphological characteristics of spores of A. koreana are rarely distinguished from Acaulospora mellea, which is reported as one of the most abundant mycorrhizal species in Korea. However, molecular evidence of rDNA sequence using improved primers for glomeromycotan fungal identification strongly supported that A. koreana is different from A. mellea but also any other species belonging to the genus Acaulospora. This is the first novel glomeromycatan fungus introduced in South Korea, but it suggests that there is a high possibility for discovering new arbuscular mycorrhizal fungi considering the abundance of plant species and advanced phylogenetic analysis technique.